If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -7y + 5 = 4y + 11 + -7y Reorder the terms: 2 + 5 + -7y = 4y + 11 + -7y Combine like terms: 2 + 5 = 7 7 + -7y = 4y + 11 + -7y Reorder the terms: 7 + -7y = 11 + 4y + -7y Combine like terms: 4y + -7y = -3y 7 + -7y = 11 + -3y Solving 7 + -7y = 11 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 7 + -7y + 3y = 11 + -3y + 3y Combine like terms: -7y + 3y = -4y 7 + -4y = 11 + -3y + 3y Combine like terms: -3y + 3y = 0 7 + -4y = 11 + 0 7 + -4y = 11 Add '-7' to each side of the equation. 7 + -7 + -4y = 11 + -7 Combine like terms: 7 + -7 = 0 0 + -4y = 11 + -7 -4y = 11 + -7 Combine like terms: 11 + -7 = 4 -4y = 4 Divide each side by '-4'. y = -1 Simplifying y = -1
| X=7(2r-3)(-14+6r) | | 2y-12-6y=5y-4-13y | | 30-5x=82 | | -32=x(-20) | | 9n+4=180 | | 5x-3x^2=1 | | We-9=22 | | ((x-1)/2)-((3x-4)/6)=1/3 | | (x-2y-1)dx-(2x-4y+3)dy=0 | | 2u-2/1-u | | 21/=3/8 | | .25x=.4x-120 | | 60x-900=-5x+3650 | | 5(x-4)(x-2)=0 | | 5x^3y^6z^2+15xy^3z^2-25x^6y^2z^3= | | X=4(-7+3r)(-4r-16) | | 14=/s | | 4(-12+7)=-76 | | log(x)+2=0 | | 40+7x=131 | | 40+7=131 | | 5+.20m=.30m | | -9n+17=-8n-3 | | 3ln(x-1)=-1 | | 13x^2+234x+1035=0 | | X=3(12-7r)(10r-5) | | T=714.28+700 | | 5a+6=9a+8 | | (m+n)+(5m-2)= | | 4x^2+26x+53=0 | | X-1=6.59 | | h=-16t^2+149t+98 |